STRATEGIES FOR DEVELOPING COMPETENT YOUTHS IN INTEGRATED AGRICULTURE THROUGH LOCAL WISDOM - Ni Made Ayu Suardani Singapurwa; I Made Kawan; Luh Suariani; Ni Made Darmadi; Ni Made Yudiastari; A.A. Made Semariyani; I Gusti Made Arjana; Ketut Agung Sudewa; I Nyoman Rudianta; Yan Tonga; Ni Putu Anom Sulistiawati (International Journal of Research in Community Services, 2023)
Integrated agricultural system is a management system (business) that combines agricultural components, such as plants, animals and fish in a unified whole. In addition to meeting the criteria for sustainable agricultural development, this system has a significant positive impact because it is organically based and developed/directed based on local potential (local resources). Warmadewa University offered a solution to the concept of integrated agricultural conservation starting from livestock and fisheries activities to post-harvest processing and encourage an entrepreneurial spirit in the younger generation. The engineering provided was an efficient technology resulting from research from professional agricultural experts that has been published in various journals. Among them are the development of organic cultivation and diversification using the SNT (System Nutrient Tank) method for exclusive vegetables, super local breed chicken farming in accordance with national poultry standards, fisheries with the concept of aquaponics (hydroponic system and poly culture system) and post-harvest processing of agricultural, livestock and fishery products, with the concept of food processing supporting local wisdom, all of which were integrated and with the concept of zero waste. The method used in this activity were delivering material, training, practice and mentoring to young people who are members of the partner, DUDI Tamiang Bali Mandiri Foundation in the Agro Learning Center (ALC) group. These youth were given integrated agricultural knowledge as well as fisheries and animal husbandry and the processing of agricultural products with the concept of "zero waste" based on Tri Hita Karana (Balinese local wisdom). There were 5 activities in this program. The output of Unwar's Matching Fund activities with the Industrial World was a young generation who are competent and have competency certificates from the Professional Certification Institute through the National Professional Certification Agency (BNSP) for 8 people, and integrated agricultural training certificates for 25 people, so they are ready to be independent or work competent in agriculture. Other outputs were Activity Books and Standard Operation Procedure Books, IPRs, Modules, Product Launches, News in the Bali Post Newspaper, Product Exhibitions, Video activities, each targeted at one achievement target.